Perceived workplace discrimination by South American immigrants in Chile: A quantitative study in a large sample - Berríos-Riquelme, José (2024)
South American immigrants in Chile constantly suffer workplace discrimination, which is usually related to different variables that are inherent to their immigration process. The objective of this article was to evaluate perceived workplace discrimination by South American immigrants in Chile. A cross-sectional design with a descriptive scope was used, where the final sample was made up of 612 South American immigrants of legal age who have been living in the country for more than a year. The results indicate that immigrants who perceive more discrimination in the workplace are those who mainly interact with foreigners from a third nationality. Finally, the discussion is presented, contrasting the results with the theoretical framework, weaknesses and strengths of the study are analyzed, and future lines of research are suggested.